Pharmacokinetic comparison of inhaled fixed combination vs. the free combination of beclomethasone and formoterol pMDIs in asthmatic children. (15th March 2013) - Chawes, Bo L. K.; Piccinno, Annalisa; Kreiner‐Møller, Eskil; Vissing, Nadja H.; Poorisrisak, Porntiva; Mortensen, Li; Nilson, Erik; Bisgaard, Amalie; Dossing, Anna; Deleuran, Maja; Skytt, Nanna L.; Samandari, Nasim; et al.
<x xml:space="preserve">Abstract</x> Aim The fixed combination of beclomethasone (BDP) and formoterol pressurized metered dose inhaler (pMDI) (Foster®, Chiesi Farmaceutici) is being developed in the lower strength (BDP/formoterol: 50/6 μg) to provide an appropriate dosage for children with asthma. The aim of this work was to investigate the systemic bioavailability of beclomethasone‐17‐monoproprionate (B17MP, the active metabolite of BDP) and formoterol after single inhalation of Foster® pMDI 50/6 μg vs. the free combination of BDP and formoterol pMDIs in asthmatic children. Methods Children aged 5–11 years old inhaled BDP 200 μg and formoterol 24 μg as fixed vs. free combination in an open label, randomized, two way crossover single dose study. Blood was collected pre‐dose up to 8 h post‐dose for pharmacokinetic evaluation (AUC(0, t), AUC(0, ∞), AUC(0, 0.5 h, Cmax, tmax, t1/2). Pharmacodynamics included heart rate, plasma potassium, urinary glucose and cortisol excretion. Peak expiratory flow and adverse events were monitored. Results Twenty subjects were evaluable. The systemic exposure of B17MP and formoterol administered as fixed combination did not exceed the free combination: B17MP AUC(0, t) (pg ml−1 h) ratio test : reference (90% CI), 0.81 (0.697, 0.948) and formoterol AUC(0, t) (pg ml−1 h) ratio test : reference 0.97 (0.85, 1.10). All pharmacokinetic and pharmacodynamic end points showed non‐superiority in favour of the test drug. One adverse event (vertigo) occurred but was not considered treatment‐related. Conclusion BDP and formoterol pharmacokinetic and pharmacodynamic effects are non‐superior after administration of the two actives as fixed vs. the free combination in 5–11‐year‐old asthmatic children.